1998
DOI: 10.1136/gut.42.1.76
|View full text |Cite
|
Sign up to set email alerts
|

Predictive factors for survival of patients with inoperable malignant distal biliary strictures: a practical management guideline

Abstract: Background-Stenting is the treatment of choice for inoperable malignant strictures of the common bile duct. Criteria for the choice of stents (plastic versus metallic) remain controversial because predicting survival is diYcult. Aims-To define prognostic factors in order to improve the cost eVectiveness of endoscopic palliation. Patients-One hundred and one patients were included in a prospective trial. Seven prognostic variables for survival were analysed (age, sex, bilirubinaemia, weight loss, presence of li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
58
0
8

Year Published

2001
2001
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(68 citation statements)
references
References 21 publications
2
58
0
8
Order By: Relevance
“…Studies comparing surgical to non-surgical biliary drainage showed similar overall palliative effects but with higher perioperative morbidity and mortality [263,264] . Surgical drainage has the advantage of superior patency rates and prevents the need for stent exchanges required when using endoscopic or percutaneous stents due to clogging [265] . Currently, the main candidates for surgical drainage are patients found to have unresectable CC at the time of exploration, individuals who are not able to undergo repeat endoscopic or percutaneous stent exchanges, and those who have long expected survival and who are fit for surgery [183,266] .…”
Section: Surgical Biliary Drainagementioning
confidence: 99%
“…Studies comparing surgical to non-surgical biliary drainage showed similar overall palliative effects but with higher perioperative morbidity and mortality [263,264] . Surgical drainage has the advantage of superior patency rates and prevents the need for stent exchanges required when using endoscopic or percutaneous stents due to clogging [265] . Currently, the main candidates for surgical drainage are patients found to have unresectable CC at the time of exploration, individuals who are not able to undergo repeat endoscopic or percutaneous stent exchanges, and those who have long expected survival and who are fit for surgery [183,266] .…”
Section: Surgical Biliary Drainagementioning
confidence: 99%
“…Case 5 is, however, a fascinating example of someone who declined conventional treatment of a cancer that untreated would have reduced the patient's survival to 3.2 to 6.6 months. 11,12 While on the Gerson regimen, he experienced a very slowly progressing cancer and a 6-year survival. Furthermore, case 4 had only 1 cycle of chemotherapy, unlikely to have sufficiently managed her lymphoma.…”
Section: Discussionmentioning
confidence: 99%
“…Type IV lesion are generally considered to be unresectable (6). Approximately 80% to 90% of these patients will be found unresectable (3,7,10,11). Prognosis of latter patients is dismal.…”
Section: The Treatment Options In Malignant Biliary Obstructionmentioning
confidence: 99%
“…At the time of diagnosis, 90% of patients with malignant obstruction of bile ducts may benefit from palliative treatment only and have a very poor prognosis (3,7). Palliation of unresectable malignancies requires a multidisciplinary approach including medical oncologists, radiation oncologists, gastroenterologists, hepatobiliary surgeons, and interventional radiologists.…”
Section: Introductionmentioning
confidence: 99%